2022
DOI: 10.1088/1742-6596/2217/1/012031
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of radial thrust fluctuation caused by diffuser rotating stall in a centrifugal pump

Abstract: In this study, in order to understand the relation between the diffuser rotating stall and the fluctuating radial thrust, unsteady RANS simulation of a centrifugal pump was carried out. The rotating stall with single stall cell was qualitatively reproduced though the propagation speed was smaller than the experiment. The pressure amplitude caused by the rotating stall was comparable to the measured one, and the tendency that the propagation speed increases as the flow rate increases agreed with experiment. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…However, at the same time, the magnitude the pressure pulsation in the pump will be significantly higher than in other cases. The numerical results of Takamine T [33] et al showed that for a centrifugal pump with guide vanes, the rotational stall phenomenon in the guide vane area will aggravate the fluctuation of the radial force of the centrifugal pump.…”
Section: Introductionmentioning
confidence: 99%
“…However, at the same time, the magnitude the pressure pulsation in the pump will be significantly higher than in other cases. The numerical results of Takamine T [33] et al showed that for a centrifugal pump with guide vanes, the rotational stall phenomenon in the guide vane area will aggravate the fluctuation of the radial force of the centrifugal pump.…”
Section: Introductionmentioning
confidence: 99%